1992
DOI: 10.1002/j.1537-2197.1992.tb13680.x
|View full text |Cite
|
Sign up to set email alerts
|

Allozyme Diversity Within and Divergence Among Four Species of Robinsonia (Asteraceae: Senecioneae), a Genus Endemic to the Juan Fernandez Islands, Chile

Abstract: Enzyme electrophoresis was employed to assess genetic diversity within and divergence among four species of Robinsonia (R. evenia, R. gayana, R. gracilis, R. thurifera), a genus endemic to the Juan Fernandez Islands, Chile. The genus consists of treelike perennial plants, and all species are dioecious. Morphological diversity within the genus is reflected by recognition of two subgenera, with three sections in one subgenus. Total gene diversity is highest in the two species (R. gayana and R. gracilis) that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Studies from the flora of the Juan Fernández Islands also support the idea of high initial rates of radiation, with faster rates evident on the younger island: 0.33 species per lineage per million years on Mastierra (island age: 4 Myr) vs. 0.96 species per lineage per million years on Masafuera (island age: 1-2 Myr) (Levin, 2000;cited in Levin, 2004). Electrophoretic data for the endemic genus Robinsonia (Asteraceae) suggest that the founding population arrived early in the 4.0-million-year history of Masatierra Island, radiating and speciating rapidly after colonization (Crawford et al, 1992). Similarly, Kaneshiro et al (1995, p. 71), in their analysis of species groups within the picture-wing Drosophila of Hawaii, make the following observation: 'Most of these species, like many other extant terrestrial endemic fauna, show a very strong but by no means exclusive tendency to single-island endemism.…”
Section: General Evaluation Of the General Dynamic Modelmentioning
confidence: 99%
“…Studies from the flora of the Juan Fernández Islands also support the idea of high initial rates of radiation, with faster rates evident on the younger island: 0.33 species per lineage per million years on Mastierra (island age: 4 Myr) vs. 0.96 species per lineage per million years on Masafuera (island age: 1-2 Myr) (Levin, 2000;cited in Levin, 2004). Electrophoretic data for the endemic genus Robinsonia (Asteraceae) suggest that the founding population arrived early in the 4.0-million-year history of Masatierra Island, radiating and speciating rapidly after colonization (Crawford et al, 1992). Similarly, Kaneshiro et al (1995, p. 71), in their analysis of species groups within the picture-wing Drosophila of Hawaii, make the following observation: 'Most of these species, like many other extant terrestrial endemic fauna, show a very strong but by no means exclusive tendency to single-island endemism.…”
Section: General Evaluation Of the General Dynamic Modelmentioning
confidence: 99%
“…PAGE: Leaves were ground in a 160 mM tris/107 mM glycine/ HCl-buffer, pH 8.0 (including 20 % sucrose, 1 % DTT, 0.1 % mercaptoethanol, and bromophenol blue). MDH was resolved in a 7.5 % gel (acrylamide/bisacrylamide 19 : 1) in Hoefer Mighty (1) only understorey (2) about 1 month after mowing Mini SE250 chambers. A 250 mM tris/boric acid buffer, pH 8.0, was used for gel and bridge.…”
Section: Isozymesmentioning
confidence: 99%
“…Dolan (1994 [4] ) found potential negative impacts of small population sizes in a genetically depauperate subset of the whole sample. In comparing narrow island endemics, Crawford et al (1992 [2] ) found lowest genetic diversity in the smallest populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, among insular plants, the lower minimum I values have been barely recorded in very limited 'congeneric' or 'intergeneric' population pairs of the large complex of morphologically and ecologically highly radiating taxa; e.g., Alsinoideae in Hawaii (0.242; Weller, Sakai and Straub, 1996), for silversword alliance in Hawaii (0.426; Witter and Carr, 1988), for woody Sonchus alliance in Canary (0.490; Kim et al, 1999) and Robinsonia in Juan Fernandez (0.560; Crawford et al, 1992). Unlike morphological and ecological phenotypes, protein molecules like allozyme are assumed to evolve much constantly because of their neutrality to natural selection, i.e., the neutral theory of molecular evolution (Kimura, 1983).…”
Section: Allozyme Diversity and Origin Of L Longiflorummentioning
confidence: 99%